Hysteresis properties of hexagonal arrays of FePd nanowires - Viqueira, María Soledad (2013)
FePd nanowires (NWs) with different compositions have been grown into anodized aluminum oxide templates (AAO) by AC electrodeposition at room temperature. The effects of nanowire composition and morphology on the hysteresis properties of the ordered array of NWs are investigated. All the NWs are polycrystalline; the Fe-rich wires have a bcc structure while the Pd rich ones are fcc. FePd NWs are ferromagnetic and the spontaneous magnetization is found to be parallel to the nanowire long axis (out of plane easy axis) and both, the saturation polarization and the coercive field increase with the iron content.